Aplikasi Bantuan Sosial Tunai Masyarakat Kurang Mampu di Desa Tanjung Dalam Berbass Web - elpiani, desi; Suhartini Suhartini; Hepny Samosir (Jurnal Publikasi Teknik Informatika, 2023)
Tanjung Dalam Village is one of the government institutions located under the auspices of the Rambang Village, Muara Enim District. The method of processing data on cash social assistance, at this institution still uses the manual method which causes frequent errors, resulting in inaccurate data. In addition, the manual method must go through a long process and requires a relatively long time, as well as insecure data storage. The purpose of this research is to build an application using a website to make it easier for Tanjung Dalam Village to process cash social assistance, because well computerized and easy to use. The research method uses a qualitative descriptive method with data collection techniques in the form of observation, interviews and literature study. The type of data consists of qualitative data and data sources consist of primary and secondary data. Methods of developing activity diagram tools. This application was built using a website with the PHP programming language and MySQL database, and to print reports using a pdf component.